Exploring the Impact of the Somatic Method ‘Timani’ on Performance Quality, Performance-Related Pain and Injury, and Self-Efficacy in Music Students in Norway: An Intervention Study - Détári, Anna; Nilssen, Tina Margareta (Frontiers in Psychology, 2022)
The importance of including performance-related body mechanics into music education to improve performance quality and prevent performance-related injuries has been stressed by many researchers recently. However, it is unclear how this information could be delivered most effectively. The somatic method ‘Timani’ provides a practical solution by combining expertise in music performance and functional body mechanics with the goal of achieving a more efficient playing technique. Since no in-depth study has been conducted to assess the method before, we explored the impact of this method on young musicians’ performance through an online, four-week-long Timani intervention with a mixed-methodology design. 17 students (mean age = 19.17 years) were recruited from the Norwegian Academy of Music. They participated in two group workshops at the beginning and the end of the project and received four individual Timani sessions administered by certified teachers. We collected survey data at the workshops about performance-related pain and self-efficacy, and qualitative feedback after each session. In addition, all sessions were observed by the researcher and semi-structured interviews were conducted with the teachers about the perceived outcomes and their experiences with teaching the method online. Our findings show that the intervention had a positive impact on a physical, professional, and to some extent, psychological and behavioural level. The improvements included better posture when playing, enhanced control and dexterity in the upper extremities, and improved breathing mechanisms. The seven students who had performance-related pain pre-intervention reported a reduction in the discomfort. The positive results were achieved by the dual expertise of the teachers in music performance and functional body mechanics, the structure of the sessions, the communication, and the pedagogical tools used. Both students and teachers felt that administering the sessions online was satisfactory and produced good results. Timani is a promising method to establish healthy playing and singing habits thus improving performance quality and preventing performance-related problems, and has great potential in reducing pre-existing injuries and pain. Also, it can be effectively taught online which has further implications for the logistics of delivery.